Population abundance Tetraclita Panamensis (Cirripedia: Tetraclitidae) under two different wave conditions in Palma Island, Colombian Pacific (Revista de Investigaciones Universidad del Quindío, 2011)
The populations of barnacles as Tetraclita panamensis are subject to biotic and abiotic factors in the vertical intertidal zone, and are also susceptible to the horizontal conditions as the waves. This study focused on assessing the horizontal abundance and vertical distribution of T. panamensis under conditions of strong and calm waves, and temperature in Palma Island (Colombian Pacific) as an indirect measure of adaptation to these conditions. Thirty plots were conducted in the western side and 34 in the eastern, in a systematic way, in which there were 1239 and 1156 individuals respectively. Populations of both sides of the island did not differ significantly (p = 0.319); this suggests that populations of T. panamesis are adapted to wave conditions, while the vertical distribution may be influenced primarily by physical and biological conditions of the land that reduce the effects of temperature and humidity. Currently, there are not enough studies that show that the wave is affecting the settlement and recruitment of barnacles in Isla Palma, and also, in some way their distribution.
Keywords: abundance; adaptation; barnacles; waves; temperature